2010
DOI: 10.1002/dc.21571
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 immunocytochemical staining increases sensitivity in the routine cytologic evaluation of biliary brush specimens

Abstract: Biliary brush cytology is an important diagnostic tool in the evaluation of biliary strictures. Here, we evaluated 64 patients with biliary strictures who underwent endoscopic retrograde cholangiopancreatography with bile duct brushings. We assessed the utility of combining routine Papanicolaou-stained cytologic evaluation with immunocytochemical expression of insulin-like growth factor mRNA-binding protein-3 (IMP3). Definitive diagnoses were obtained via tissue resection/autopsy, biopsy, fine needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
2
25
1
Order By: Relevance
“…Our test sensitivity rate is at the lower end of the spectrum of some previously reported in the literature (range, 30%-68%), [14][15][16] but it is higher than rates reported by others (6%-33%), [3][4][5]7,8,22 which could be the result of several factors, some of which we explored in detail.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Our test sensitivity rate is at the lower end of the spectrum of some previously reported in the literature (range, 30%-68%), [14][15][16] but it is higher than rates reported by others (6%-33%), [3][4][5]7,8,22 which could be the result of several factors, some of which we explored in detail.…”
Section: Discussioncontrasting
confidence: 64%
“…1,2 Most studies on bile duct brushings (BDBs) agree that the sensitivity of this modality is fairly low, although the numbers vary substantially from 6% to 64%, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and the factors implicated in the test's inaccuracies are also significantly different. These variations are presumably related to case definition (identification) as well as the setting in which the studies were performed and the different methods of specimen processing used.…”
mentioning
confidence: 99%
“…Normal adult tissues do not contain immunohistochemically detectable levels of IMP3, but its expression is significantly upregulated in different human malignancies including adenocarcinomas of various origins [13,14,15,16,17,18,19,20,21,22]. These findings suggest that immunohistochemical analysis of IMP3 expression can be used to differentiate benign processes from malignant processes in different organs and specimens [23,24,25]. Yantiss et al [23] and Wachter et al [24] examined the diagnostic value of immunohistochemical IMP3 expression in fine-needle aspiration and core-needle biopsies of pancreatic ductal adenocarcinoma, respectively, and concluded that IMP3 is a promising new marker with high specificity and sensitivity for pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Because IMP3 is overexpressed in malignant tumors but is rarely detectable in normal adult tissues, immunohistochemical analysis of IMP3 expression can be used to differentiate benign and malignant processes [23,24,25]. However, studies on the usefulness of IMP3 for the detection of malignant cells in effusions are limited [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Cytoplasmic positivity has been demonstrated in 71% to 97% of pancreatic ductal adenocarcinomas in various studies including cytology specimens, 162,167,[172][173][174][175][176][177] 82% of gallbladder adenocarcinomas, 168,178 and 50% to 92% of a d enoca rcino ma s o f ex tr a hep a tic b ile ducts. 169,170,[178][179][180] Intrahepatic cholangiocarcinomas also overexpress IMP3 at a high frequency (82%-90%), 167,181 but lower frequencies (37%-41%) are also reported. 178,182 In our experience, the greatest advantage of IMP3 is its high specificity for malignancy (Figure 11, B).…”
mentioning
confidence: 99%